Accused, exiled, acquitted: surviving witchcraft charges in colonial New England - Jansonius, Makenzie Renee (My University, 2025)
By analyzing individual trials rather than collective panics, this study reveals the calculated nature of witchcraft accusations in maintaining social order amid frontier conflicts, imperial tensions, and religious anxieties through the case studies of three colonial women: Mary Staples of Fairfield, CT, Katherine Harrison of Wethersfield, CT, and Mary Webster of Hadley, MA. Unlike most scholarship surrounding the witch trials that took place in New England during the 17th century, this research investigates how these women successfully navigated the witchcraft accusations brought against them. Building upon gendered analyses pioneered by Carol F. Karlsen while incorporating the legal and regional approaches utilized by more recent scholarship in the field, this thesis seeks to demonstrate that witch trials functioned as a way to eliminate specific socially marginalized individuals rather than cull divergence in one fell swoop. The cases of Mary Staples, Katherine Harrison, and Mary Webster reveal the ways in which accusations of witchcraft functioned as tools of social control wielded against those that defied community norms. The Puritan elite’s near-obsession with diabolism coupled with the laity’s preoccupation with maleficium created a volatile legal and social landscape in which accusations were simultaneously religiously, personally, and politically motivated. Studying women who survived the accusations against them provides unique insights that would be unavailable when focusing on only the trials that ended in execution. The three case studies I have chosen highlight the limitations of patriarchal power structures and reveal points of flexibility within seemingly rigid systems. The cases of Staples, Harrison, and Webster highlight the agency of the accused, revealing how women actively participated in their own defense.
Keywords: Witchcraft; Witch trials; Mary Staples; Katherine Harrison; Mary Webster; Connecticut River Valley